An adaptive and versatile method to quantitate and characterize collective cell migration behaviors on complex surfaces - Loesel, Kristen E.; Hiraki, Harrison L.; Baker, Brendon M.; Parent, Carole A. (Frontiers in Cell and Developmental Biology, 2023)
Collective cell migration is critical for proper embryonic development, wound healing, and cancer cell invasion. However, much of our knowledge of cell migration has been performed using flat surfaces that lack topographical features and do not recapitulate the complex fibrous architecture of the extracellular matrix (ECM). The recent availability of synthetic fibrous networks designed to mimic in vivo ECM has been key to identify the topological features that dictate cell migration patterns as well as to determine the underlying mechanisms that regulate topography-sensing. Recent studies have underscored the prevalence of collective cell migration during cancer invasion, and these observations present a compelling need to understand the mechanisms controlling contact guidance within migratory, multicellular groups. Therefore, we designed an integrated migration analysis platform combining tunable electrospun fibers that recapitulate aspects of the biophysical properties of the ECM, and computational approaches to investigate collective cell migration. To quantitatively assess migration as a function of matrix topography, we developed an automated MATLAB code that quantifies cell migration dynamics, including speed, directionality, and the number of detached cells. This platform enables live cell imaging while providing enough cells for biochemical, proteomic, and genomic analyses, making our system highly adaptable to multiple experimental investigations.